Natural gas hydrates a guide for engineers - Carroll, John J., 1958- (Gulf Professional Publishing, 2014)
This updated edition helps managers and engineers get up to speed on all the most common hydrate types, how to forecast when they will appear, and safely mitigate their removal. Topics covered include: new hydrate types and formers, including mercaptans and other sulfur compounds; information on how to handle hydrate formation in the wellbore, useful information in light of the Macondo explosion and resulting oil spill; detailed phase diagrams, such as ternary systems, as well as more relevant multicomponent mixtures; how to quantifiably measure the conditions that make hydrates possible and mitigate the right equipment correctly; how to predict and examine the conditions at which hydrates form with simple and complex calculation exercises; and knowledge and review lessons learned from new real-world case studies and examples, covering capital costs, dehydration, and new computer methods. -- Edited summary from book.
Keywords: Natural gas -- Hydrates.; Hydrates -- Analysis.; elektronické knihy; electronic books